Avaliação da associação de células da fração mononuclear de medula óssea com biomaterial na regeneração de úlceras cutâneas em modelo experimental com diabetes - Mazzuca, Rafael dos Santos (2017)
Everyyear the number of people with diabetes increases considerably. By the year 2014, more than 414 million cases of the disease have been registered worldwide. A major problem is the increasing number of diabetic patients who develop ulcers in the lower limbs, a complication mainly due to inadequate glycemic control, besides the imbalance in the inflammatory phase during the process of tissue regeneration, which often leads to amputation of the lower limbs.The increase number ofcases andcomplications derived from the diabetesrequire the development of new therapeutic strategies to minimize the development of these ulcers to more severe cases new therapeutic strategies are necessary, aiming to minimize the development of these ulcers thatleads to a poor quality of life due to ulcers, and ultimately, amputations. Cell therapy associated with the use of biomaterials, produced through tissue engineering processes, represents a new alternative for current treatments. The use of bone marrow mononuclear cells has shown to be an important ally for the healing process, since they are a good quality and abundant cells of easy access. The purpose of this study was to evaluate whether the use of a biomaterial as a biological dressing, associated or not with bone marrow mononuclear cells, would improve the regenerative response of ulcer lesions, reducing the time of healing.Streptozotocin was used to induce diabetes in Wistar rats. To simulate an ulcer wound, a punch was created on the animal's back.Themacroscopic analysishave shown that the animals treated with the biomaterial associated with the bone marrow mononuclear cells, had a significantly better regeneration rate in the first 2 days after the formation the wound formation, when compared with the other groupswhere only the biomaterial was applied or did not received any treatment.In addition, histological sections stained with hematoxylin and eosin, allowed to define the degree of regeneration that each animalhave undergone, taking into account the reepithelialization and abundance of inflammatory infiltrate.Our results indicate that the use of the bone marrow mononuclear cellsfraction associated with the biomaterial may be a therapeutic ally in the regeneration of diabetes ulcers.